2013
DOI: 10.1590/s0100-40422013000700013
|View full text |Cite
|
Sign up to set email alerts
|

Emissões de óxido nitroso do tanque de aeração de uma estação de tratamento de esgotos com sistema de lodos ativados convencional

Abstract: Recebido em 26/10/12; aceito em 24/3/13; publicado na web em 14/5/13 NITROUS OXIDE EMISSIONS FROM THE AERATION TANK OF A WASTEWATER TREATMENT PLANT WITH CONVENTIONAL ACTIVATED SLUDGE PROCESS. Nitrous oxide (N 2 O) emissions were measured monthly from January to June 2010 in the aeration tank of a wastewater treatment plant (WWTP) in Southeast Brazil. Emissions were lower in summer than winter and were positively related with influent ammonium (NH 4 + ) concentration. The average N 2 O emission was 1.11 kg N da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…However, there is a high variability in emission factors (EFs) (0-25%), based on the load of the influent total nitrogen (TN), available in the literature from studies performed directly at WWTPs (Kampschreur et al, 2009;Law et al, 2012a). This variability is often attributed to the particularities related to operational parameters adopted at the different WWTPs studied, highlighting among them, the organic matter and TN to be treated, sludge age, dissolved oxygen (DO) concentration and aeration rate (Kampschreur et al, 2009;Brotto et al, 2010;Brotto, 2011;Law et al, 2012a;de Mello et al, 2013;Ribeiro et al, 2013). Recently, Daelman et al (2013) reported that different sampling strategies used at the WWTPs studied can also play an important role as an influencing factor in the observed variability in EFs of N 2 O.…”
Section: Tropospheric Nitrous Oxide (N 2 O)mentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is a high variability in emission factors (EFs) (0-25%), based on the load of the influent total nitrogen (TN), available in the literature from studies performed directly at WWTPs (Kampschreur et al, 2009;Law et al, 2012a). This variability is often attributed to the particularities related to operational parameters adopted at the different WWTPs studied, highlighting among them, the organic matter and TN to be treated, sludge age, dissolved oxygen (DO) concentration and aeration rate (Kampschreur et al, 2009;Brotto et al, 2010;Brotto, 2011;Law et al, 2012a;de Mello et al, 2013;Ribeiro et al, 2013). Recently, Daelman et al (2013) reported that different sampling strategies used at the WWTPs studied can also play an important role as an influencing factor in the observed variability in EFs of N 2 O.…”
Section: Tropospheric Nitrous Oxide (N 2 O)mentioning
confidence: 99%
“…De Mello et al (2013) estimated, through a study at an intermittent aeration activated sludge system of an urban WWTP, with cycles of 60 minutes with aeration and 30 minutes without aeration, that 50-75% of the net production of N 2 O was emitted to the atmosphere during the aeration step (aerobic condition). Foley et al (2010) and Ribeiro et al (2013) suggested that lower N 2 O emissions are related to the higher removal efficiency of TN when there is complete nitrification and denitrification processes. In a study performed at an activated sludge WWTP with modified aeration, Brotto (2011) found that the sludge age influenced the nitrification process.…”
Section: Tropospheric Nitrous Oxide (N 2 O)mentioning
confidence: 99%
See 3 more Smart Citations